2020
DOI: 10.1016/j.jaac.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

High Psychopathology Subgroup in Young Children With Autism: Associations With Biological Sex and Amygdala Volume

Abstract: The aims of this study were to identify a subset of children with autism spectrum disorder (ASD) and co-occurring symptoms of psychopathology, and to evaluate associations between this subgroup and biological sex and amygdala volume. Method: Participants included 420 children (ASD: 91 girls, 209 boys; typically developing controls: 57 girls, 63 boys). Latent profile analysis was used to identify ASD subgroups based on symptoms of psychopathology, adaptive functioning, cognitive development, and autism severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…More interestingly, divergence in the brain‐behavior patterns was found in studies using other symptom measures. For example, Nordahl et al (2020) used behavioral performance in an internalizing task to measure autistic symptoms and reported an association between GM volume in the right amygdala and internalizing behaviors. Using the Social Responsiveness Scale (SRS) to measure autistic traits, Cauvet et al (2020) showed that GM volume and cortical thickness of the brain regions corresponding to the social brain network were related to autistic symptoms among both females and male with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, divergence in the brain‐behavior patterns was found in studies using other symptom measures. For example, Nordahl et al (2020) used behavioral performance in an internalizing task to measure autistic symptoms and reported an association between GM volume in the right amygdala and internalizing behaviors. Using the Social Responsiveness Scale (SRS) to measure autistic traits, Cauvet et al (2020) showed that GM volume and cortical thickness of the brain regions corresponding to the social brain network were related to autistic symptoms among both females and male with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that none of these studies, including ours, were specifically designed to test for sex differences. This may be important as studies aimed at understanding sex differences have reported relatively large differences between sexes, for example, a study of toddlers with ASD found that females were almost two times more likely to present with high psychopathology as compared to males [Nordahl et al, 2020]. Future studies with larger samples of females may be warranted to more conclusively determine the role of sex in emotion dysregulation and use of psychiatric services.…”
Section: Discussionmentioning
confidence: 99%
“…The GAIN study has an identical study design to the APP and enriches the predominantly male APP cohort with additional female participants. The study protocols, including recruitment and behavioural assessments for the APP and GAIN studies, have been previously described in detail 58 60 . All assessment measures described below were conducted as part of the APP and GAIN study protocols during enrolment in these studies.…”
Section: Methodsmentioning
confidence: 99%